Features of the edaphotopes in the technogenous ecotopes (CHORNOMORSKI BOTANICAL JOURNAL, 2016)
The results of the study showed that all industrial sites of metallurgical and coking plants, sludge dumps are characterized by alkaline or strongly alkaline reaction of the substratum, which is almost unchanging on the territory of the ecotope. For this index the most unfavorable conditions were developed on the territory of Enakiev Metallurgical Plant and sludge dumps of Donetsk Metallurgical Plant. The strong alkaline reaction of the substratum in most cases is the limiting factor for the growth of plants. Analysis of the type and degree of salinity showed no salinity of all the studied samples with a predominance in the consist of sulfate ions and calcium ions. The amount of absorbed bases of the substrate studied technogenic ecotopes ranges from 4.35–23.60 mgekv / 100 g of the rock. The lowest values was recorded in the dumps substrates of the Nikitovsky hydrargyrum plant, Enakievo Metallurgical plant and sludge dumps of Donetsk Metallurgical Plant. The highest values of absorbed bases were observed on the territory of Avdeevka coke plant, which is confirmed by the presence on the territory of plant communities.
Keywords: edaphotope, pH, salinity, technogenous ecotope.